Coexisting iodine avid and iodine nonconcentrating lesions with multiple distant soft tissue metastasis in papillary thyroid cancer - Mohapatra, Tushar (Medknow Publications & Media Pvt Ltd, 2012)
Distant soft tissue metastasis and the simultaneous presence of iodine concentrating and nonconcentrating lesions in papillary thyroid cancer are extremely rare. The concerned patient, a histopathologically proven case of papillary thyroid cancer with nodal metastases treated with total thyroidectomy, bilateral cervical nodal dissection, and radioablation, subsequently developed lung, muscle, and liver metastasis. Triggered by increased thyroglobulin, the iodine-131 whole body scan and 200 mci iodine-131 post-therapy scan showed a left gluteus maximus lesion and a liver lesion. Fludeoxyglucose (FDG) positron emission tomography-computed tomography (PET-CT) scan intended to find additional lesions revealed iodine and FDG nonconcentrating bilateral pulmonary nodules and a single FDG avid hepatic and two muscle metastases. Although FDG concentration in metastatic pulmonary nodules is generally low, the CT characteristics were classical for metastatic lesion. A follow-up FDG PET-CT study six months after 200 mci iodine-131 radioablation showed treatment response in muscle and liver lesions but not lungs.